Confiscation of assets without a criminal decision in recovering state financial losses due to crime of corruption - Muhamad Yodi Nugraha; Nur Azisa; Haeranah Haeranah (IHSA Institute, 2023)
The focus of this study is a Juridical Review of the Concept of Confiscation of Assets Without a Criminal Decision (Non-Coviction Based Asset Forfeiture) in Recovering State Financial Losses Due to Crime of Corruption. This study aims to analyze and find answers about the legal implications of the application of the concept of non-conviction based asset forfeiture to the current criminal system of corruption and to find answers about the ideal concept in forfeiture of assets without, legal basis, and legal doctrine to review the issues under study. The results showed that (1) the implications of the application of the concept of non-conviction based asset forfeiture to the current corruption crime conviction system (2) the ideal concept of asset forfeiture without a conviction verdict to maximize the return of state financial losses is to establish a special legal regime on non-conviction based on asset forfeiture through a law.